PERSEPSI DAN TINGKAT PENGETAHUAN PASIEN PENYAKIT JANTUNG TERHADAP COVID-19 DI RUMAH SAKIT MITRA MEDIKA AMPLAS MEDAN - FAWWAZ, ADITYA ACHMAD; HANDAYANI, AHMAD (JURNAL ILMIAH SIMANTEK, 2023)
COVID-19 is a respiratory disease caused by Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2). This disease causes people to be afraid to go to the hospital. The fear also affects the number of heart patients who go to hospital. This study aims to determine the perception and knowledge of heart patients about COVID-19. The method used is descriptive-quantitative with a cross-sectional study design. Cardiac patients who were treated at Mitra Medika Amplas Hospital in Medan were included in the inclusion criteria. The research data was obtained from primary data using the COVID-19 knowledge questionnaire and the COVID-19 perception questionnaire. The researcher found that the knowledge of 96 respondents was good, with a total of 100%. Respondents' perception of COVID-19 is good, with a total of 99%. It was concluded that patients receiving treatment and being treated at the Mitra Medika Amplas Hospital in Medan had good knowledge and perceptions about COVID-19.